EFFECTIVENESS OF ELECTROMAGNETIC RADIATION OF EXTREMELY HIGH FREQUENCIES USAGE IN COMPLEX TREATMENT OF YOUTHS WITH CARDIAC PATHOLOGY AT SANATORIUM-PREVENTORIUM CONDITIONS - Moroz, G.A. (World of Medicine and Biology, 2013)
Functional changes in organism in 36 youths (16-17 years old) with cardiac pathology of non-rheumatic origin and concomitant changes in thyroid gland under complex treatment with electromagnetic radiation of extremely high frequencies usage at sanatorium-preventorium conditions are investigated (comparative analysis) in current study. The results of investigation showed favourable effect – ascension of cardiac hemocirculation condition, improvement of vegetative regulation of cardiac performance, and reduction of non-coordination processes of the vegetative nervous system.
Keywords: extremely high freaquency radiation therapy; cardiac pathology; youths